Causes of referred otalgia: a hospital-based study - Saraf, Aditiya; Begh, Raies Ahmad; Jyoti, Deep; Kalsotra, Parmod (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The aim of our study was to evaluate various etiologies of referred otalgia. Methods: The present study was conducted in the department of ENT, SMGS Hospital, GMC Jammu from January 2019 to January 2020. A total of 65 patients with complaint of pain in ear but normal ear examination was included in our study. All patients underwent complete ENT examination. Results: The most common cause for referred otalgia was dental pathology (58.4%), followed by pharyngitis (16.9%), tonsillitis (10.7%), supraglottic cancer (7.6%), cervical spine pathology (3.07%) and peritonsillar abscess (3.07%). Conclusions: Otalgia is a symptom with diverse causes. Though many causes are otogenic, referred pain from other regions of head and neck is also very common.